STRATEGI PENINGKATAN KEWIRAUSAHAAN BAGI MAHASISWA DI PENDIDIKAN TINGGI - M.M, Febriyanto (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2015)
Universities on the creation of labor gave the significant role, so the effect on the increasing numbers of workers. If the number of workers and jobs are not balanced, then the unemployment and economic inequality will become an increasingly urgent problem to be resolved. The number of entrepreneurs in a region that is minimal, describes the low competitiveness owned. In supporting the emergence of high competitiveness, function and the role of educators to be more active in providing motivation for learners to become entrepreneurs is indispensable. College as one of the means and facilitating role in shaping the young generation has an obligation to train and motivate the students to give to become savvy generation, independent, creative, innovative and able to create business opportunities. Thus, every college immediately towards sole discretion to balance between higher education research institutions with entrepreneurs forming institutions. Alumni are required to be innovative and creative in terms of their personal development through the creation of level playing field, so that future expected with extensive job creation, economic growth in the region will increase.Keywords: educators, labor, entrepreneurial